Enolizable Carbonyls and N, O‐Acetals: A Rational Approach for Room‐Temperature Lewis Superacid‐Catalyzed Direct α‐Amidoalkylation of Ketones and Aldehydes. Issue 17 (15th March 2016) - Touati, Bahria; El Bouakher, Abderrahman; Taillier, Catherine; Othman, Raja Ben; Trabelsi‐Ayadi, Malika; Antoniotti, Sylvain; Duñach, Elisabet; Dalla, Vincent
Abstract: An efficient catalytic room‐temperature direct α‐amidoalkylation of carbonyl donors, that is, ketones and aldehydes with unbiased N, O ‐acetals, is described. Sn(NTf2 )4 is an optimal catalyst to promote this challenging transformation at low loading and the reaction shows promising scope. A comprehensive and rational evaluation of this reaction has led to the establishment of an empirical scale of nucleophilic reactivity for a broad set of ketones that should be helpful in the synthetic design and development of carbonyl α‐functionalization methods. Abstract : Magic Lewis superacid : A room‐temperature catalytic direct α‐amidoalkylation reaction of ketones and aldehydes that operates via N ‐acyliminium ions generated in situ is reported (see scheme). This reaction is efficiently catalyzed by 0.5–2 mol % of the Lewis superacid Sn(NTf2 )4 and exhibits a large scope. An evaluation of this Mannich coupling led to the establishment of a reactivity scale of enolizable ketones.